2019
DOI: 10.3390/cancers11101559
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Oligoprogression in the Landscape of New Therapies for Metastatic Melanoma

Abstract: Background: A limited degree of progression after a response to treatment is labelled as oligoprogression and is a hot topic of metastatic melanoma (MM) management. Rogue progressive metastases could benefit from local treatment, which could allow the continuation of ongoing systemic therapy, also known as treatment beyond progression (TBP). Methods: We retrospectively reviewed 214 selected MM patients who were treated with v-Raf murine sarcoma viral oncogene homolog B (BRAF)/mitogen-activated-extracellular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Other studies have shown that surgical treatment in patients with less aggressive heterogeneous responses, such as oligometastatic progression and mixed response to therapy can render patients disease free. 13,[16][17][18] This potentially supports the added value of our clinical classification system in identifying patients who might benefit from surgical treatment in our mixed response cohort. While surgical decision-making is nuanced, our clinical practice generally supports an observation period for patients with stable disease or mixed response with re-assessment with serial imaging (usually at 3 months).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Other studies have shown that surgical treatment in patients with less aggressive heterogeneous responses, such as oligometastatic progression and mixed response to therapy can render patients disease free. 13,[16][17][18] This potentially supports the added value of our clinical classification system in identifying patients who might benefit from surgical treatment in our mixed response cohort. While surgical decision-making is nuanced, our clinical practice generally supports an observation period for patients with stable disease or mixed response with re-assessment with serial imaging (usually at 3 months).…”
Section: Discussionsupporting
confidence: 60%
“…Currently, only one study has explored the management of oligometastatic progression in metastatic melanoma, and the literature is comprised of a few individual case reports on patients with a mixed response. 13,14 Therefore, we conducted a single center retrospective study on patients with metastatic melanoma treated with first-line anti-CTLA-4 and/or anti-PD-1 therapy who developed a mixed response, defined as simultaneous tumor regression and progression, in order to identify clinicopathological characteristics, define high-risk subgroups, and assess subsequent management and outcomes.…”
mentioning
confidence: 99%
“…Melanoma at M1a stage was also a factor associated with increased PFS and OS, while the correlation between NRAS mutation and OS was consistent with evidence reporting that this genetic status is linked to better immunotherapy outcomes [31]. Likewise, we found blood cell features that may be predictive biomarkers of a response in patients to checkpoint blockade therapy, for example, a reduced leukocyte count and a higher relative lymphocyte count [2][3][4][5][6][7] were positively correlated with ORR and OS. In our study, the frequency trends of DNTs in the longitudinal analysis revealed that, beyond the expected correlations with increased CD8+ and OS, as well as in whole lymphocytes count and ORR [32], we found that for CD3+ cells, the DNT value was only significantly correlated with values that indicated a patient response.…”
Section: Discussionsupporting
confidence: 88%
“…Oligoprogression (OPD) is a relatively new concept that emerged as more effective systemic therapies became available in oncology and denotes anatomically restricted tumor progression in patients with otherwise controlled widespread disease [1]. Such an asynchronous behavior of metastatic disease has been observed in several tumor types, including melanoma, renal-cell, prostatic, and non-small-cell lung cancer (NSCLC) [1,2]. Its pathogenesis is considered to be complex, as numerous parameters, including molecular evolution of cancer cells, changes in the tumor microenvironment, hemodynamic parameters, and previous application of local therapies can potentially modulate the anatomical pattern of treatment failure.…”
Section: Introductionmentioning
confidence: 99%